Conjunctive Explanations in Science and Religion - Finnegan, Diarmid A. (Routledge Science and Religion Ser., 2023)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Contents -- Acknowledgements -- List of contributors -- Conjunctive Explanations in Science and Religion: An Introduction -- CONVERSATION I: Explanation in Science and Religion -- 1. Conjunctive Explanations: How Science and Religion Can Work Together -- Conjunctive Explanations: A Response -- 2. Agents as Difference Makers, or Why Many Human Actions Have Mental Causes -- Agents as Difference Makers: A Response -- CONVERSATION II: Designing Darwinism -- 3. The Telos of Darwin's Troubling Metaphor: Darwin's Pigeons, Dennett's Cranes, Fodor's Granny -- The Telos of Darwin's Troubling Metaphor: A Response -- 4. Asa Gray vs. Charles Darwin: Evaluating the Darwinian Case against Conjunctive Explanations -- Asa Gray vs. Charles Darwin: A Response -- CONVERSATION III: Irreducibilities, Material and Mental -- 5. God, Consciousness and Conjunctive Explanations -- God, Consciousness and Conjunctive Explanations: A Response -- 6. Complementary Causation and Emergence: A Substrate for Conjunctive Explanations -- Complementary Causation and Emergence: A Response -- CONVERSATION IV: Divine Causes and Mental Beliefs -- 7. A Conjunctive Explanation about Psychopathology? Hearing Voices, Psychosis and Religious Experience -- A Conjunctive Explanation about Psychopathology? A Response -- 8. A Conjunctive Explanation of the Mental Phenomenon of Christian Faith -- A Conjunctive Explanation of the Mental Phenomenon of Christian Faith: A Response -- CONVERSATION V: The (Im)possibility of Theological Explanations -- 9. Are Theological Explanations Superfluous? The Cognitive Science of Religion and Ockham's Razor -- Are Theological Explanations Superfluous? A Response -- 10. A Re-Evaluation of Non-Overlapping Magisteria -- A Re-Evaluation of Non-Overlapping Magisteria: A Response.